ED IDENTIFIKASI METABOLIT SEKUNDER EKO ENZIM LIMBAH BUAH DAN SAYUR : IDENTIFIKASI METABOLIT SEKUNDER EKO ENZIM LIMBAH BUAH DAN SAYUR - Bawanda, Edward Melfin; Umarudin Umarudin; Syukrianto; Galuh Gondo Kusumo; Ramadhan Renaisansa; Widya Dara Anindya; Silvi Ayu Wulansari; Vika Ayu Devianti (Jurnal Komunitas Farmasi Nasional, 2025)
Organic waste, in the form of fruit and vegetable peels from Ketintang, Surabaya City, East Java, can be processed into an eco enzyme through fermentation using a mixture of sugar and water over a period of 30 days. During this process, glucose is broken down into pyruvic acid, which, under anaerobic conditions, undergoes decarboxylation to form ethanol and carbon dioxide. This study aims to identify the secondary metabolites present in eco enzymes derived from fruit and vegetable waste. This research employed an accurate experimental method, observing colour changes in the tests for flavonoids and tannins, the presence of froth in the saponin test, the formation of rings in the steroid and terpenoid tests, and the appearance of precipitate in the alkaloid test. The analysis results indicated that the eco-enzyme from fruit and vegetable waste tested positive for flavonoids, tannins, and saponins, while alkaloids, terpenoids, and steroids were not detected (negative).